LEKSIKON ETNOMEDISIN PENYAKIT ANAK MELAYU SAMBAS - Yeyen Yeyen; Agus Syahrani; Mellisa Jupitasari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problems discussed in this research are inventory, form, lexical meaning, cultural meaning, and text supplementation of the ethnomedicinal lexicon learning of Sambas Malay children's disease into Indonesian language learning in schools. This study uses a descriptive method in a qualitative form. Data collection techniques are interviews, record and note, and documentation. This study resulted in 83 ethnomedical lexicon of Sambas Malay children's disease with the classification of disease names totaling 21 lexicon, treatment materials totaling 27 lexicon, treatment tools totaling 10 lexicon, method of making potions totaling 10 lexicon, size of material (dose) treatment amounting to 5 lexicon, and treatment process totaling 10 lexicon. The ethnomedicine lexicon of the Malay Sambas disease is monomorphemic totaling 41 lexicons, polymorphemic in the form of 10 lexicons of prefix and 12 lexicons of confixes, and 20 lexicons of phrases. The meaning of the ethnomedicine lexicon of the disease of Malay Sambas children based on the lexical meaning is 79 lexicons and 83 lexicons in culture. The form of Indonesian language learning text based on the ethnomedicine lexicon of Malay children's disease Sambas produces two learning texts, namely descriptive text and procedure text.Keywords: Lexicon, Ethnomedicine, Children's Disease, Malay Sambas.